Direct evidence of hidden local spin polarization in a centrosymmetric superconductor LaO0.55 F0.45BiS2. Issue 1 (December 2017) - Wu, Shi-Long; Sumida, Kazuki; Miyamoto, Koji; Taguchi, Kazuaki; Yoshikawa, Tomoki; Kimura, Akio; Ueda, Yoshifumi; Arita, Masashi; Nagao, Masanori; Watauchi, Satoshi; Tanaka, Isao; Okuda, Taichi
Abstract Conventional Rashba spin polarization is caused by the combination of strong spin–orbit interaction and spatial inversion asymmetry. However, Rashba–Dresselhaus-type spin-split states are predicted in the centrosymmetric LaOBiS2 system by recent theory, which stem from the local inversion asymmetry of active BiS2 layer. By performing high-resolution spin- and angle-resolved photoemission spectroscopy, we have investigated the electronic band structure and spin texture of superconductor LaO0.55 F0.45 BiS2 . Here we present direct spectroscopic evidence for the local spin polarization of both the valence band and the conduction band. In particular, the coexistence of Rashba-like and Dresselhaus-like spin textures has been observed in the conduction band. The finding is of key importance for fabrication of proposed dual-gated spin-field effect transistor. Moreover, the spin-split band leads to a spin–momentum locking Fermi surface from which superconductivity emerges. Our demonstration not only expands the scope of spintronic materials but also enhances the understanding of spin–orbit interaction-related superconductivity. The local broken symmetry induced spin-splitting in centrosymmetric materials has been predicted previously. Here the authors provide spectroscopic evidence for the coexistence of Rashba-like and Dresselhaus-like spin textures in centrosymmetric electron doped superconductor La(O, F)BiS2 .